Chapter La conservazione del patrimonio naturale e paesaggistico mediante la valorizzazione dei servizi ecosistemici offerti dal territorio: considerazioni generali e casi di studio - Lombardi, Leonardo (Territori, 2020)
Pragmatically, the same "utilitarian" vision underlying the ecosystem service paradigm seems to allow an easier understanding by large portions of society of the need to keep the ecosystems in an efficient ecological state, as shown by a series of case studies. Therefore, forms of conservation/biodiversity finance are illustrated, aimed at supporting ecosystem services, and scenarios of integration of the analysis and management of these services at the various levels of environmental planning and evaluation are presented.